Le monde en couleur de Jean Echenoz: Les termes de couleurs dans Je m'en vais et leur traduction hongroise - Laky, Krisztina (Verbum – Analecta Neolatina, 2012)
This study investigates whether or not color naming in translation is indicative of cultural differences. After a short introduction into the realm of colors, this paper briefly summarizes current thinking on issues of color naming and its impact on translation. This is followed by a review of the use and symbolism of the different color terms in Jean Echenoz's novel Je m'en vais and a comparative analysis of the original novel and its Hungarian translation from the point of view of color naming.